2021
DOI: 10.1111/josh.13011
|View full text |Cite
|
Sign up to set email alerts
|

Homeschool Student Physical Activity Compared to Public/Private School Students: The 2017 US National Household Travel Survey

Abstract: BACKGROUND School is an important place for physical activity (PA); however, little is known about how homeschool students' PA levels compare with public and private school students. This study estimated the national prevalence of PA levels of homeschool students compared to public and private school students. METHODS We used the 2017 National Household Travel Survey for school‐aged participants (N = 31,486) to compare weekly PA (not active, light or moderate activity, or vigorous activity) by school type (pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Globally, there appear to be marked socioeconomic disparities between students in public and public schools [91]. Any walking and any MVPA did not differ between school types for high school or middle school parents [92]; however, the results of the present study show data in favour of public school ownership in total sleep time and time in bed as well as lower sedentary behaviour, but not in sleep efficiency in those performing PAS, relative to privately owned schools.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Globally, there appear to be marked socioeconomic disparities between students in public and public schools [91]. Any walking and any MVPA did not differ between school types for high school or middle school parents [92]; however, the results of the present study show data in favour of public school ownership in total sleep time and time in bed as well as lower sedentary behaviour, but not in sleep efficiency in those performing PAS, relative to privately owned schools.…”
Section: Discussioncontrasting
confidence: 72%
“…In private schools, there are a high percentage of schools on the outskirts of population centres or cities, which makes it difficult for them to engage in daily physical activity on the way to the school, and this could be a determining factor in the differential values of APL in those who do not do PSA. On the other hand, sleep values may be related to the pressure, anxiety and amount of homework [93] that the private system, as opposed to the public system, imposes on its students, which, as the literature indicates, increases the probability of suffering from sleep disorders, along with sedentary behaviour [91].…”
Section: Discussionmentioning
confidence: 99%
“…One study of homeschooled middle and high school students prepandemic found that homeschooled children were more likely to engage in no PA than were students in public or private brick and mortar schools. 13 Though not addressing PA levels, a Texas study of children aged 5-17 years found no relationship between measures of weight status or physical fitness and length of time homeschooling. 14 Finally, pre-pandemic studies suggest that children are typically more physically active in the spring and summer months.…”
mentioning
confidence: 98%
“…The profound shift in educational modalities seen during COVID‐19, where more children were taking classes from home, provides a unique opportunity to understand how in‐person and remote or home‐based learning environments differ in terms of support for healthy lifestyle behavior patterns. One study of homeschooled middle and high school students pre‐pandemic found that homeschooled children were more likely to engage in no PA than were students in public or private brick and mortar schools 13 . Though not addressing PA levels, a Texas study of children aged 5‐17 years found no relationship between measures of weight status or physical fitness and length of time homeschooling 14 …”
mentioning
confidence: 99%